Book Review: "The Responsibility to Understand: Hermeneutical Contours of Ethical Life" by Professor Theodore George - Graham McCaffrey (University of Calgary, 2020)
This article is a review of Dr. Theodore George’s new book, The Responsibility to Understand: Hermeneutical Contours of Ethical Life (2020) from the viewpoint of applied hermeneutics and practice professions, especially nursing. I highlight aspects of the book that speak most directly to applied hermeneutics, including Figal’s version of objectivity, and the need to allow displacement to open space for new understanding. I discuss points that I think are open to continuing debate, including the question of whether hermeneutics is being presented as an ethics in itself, or as a gateway to ethical decision making that has to be determined by other values. For practice professions that are conspicuously bounded by regulations of various kinds, it is a feature of ethical life that has to be taken into account. Another question, is whether George’s analysis of solidarity, pushing back against impersonal, calculative values penetrating modern life, sufficiently captures the fervour of closed solidarities that have sprung up as reaction and adjunct to those same values. I suggest that George’s chapter on translation could provide a stimulating starting point for a hermeneutic analysis of “knowledge translation” in research. The conclusion is that George’s book is an excellent addition to the hermeneutic literature, post-Gadamer, that extends a welcome to those of us working in applied hermeneutics, inviting us into a thought provoking and creative conversation.